Anti-Nostalgia e a Masculinidade Tóxica na obra de Michel Laub e Luiz Ruffato - Nielson, Rex P. (REVELL - REVISTA DE ESTUDOS LITERÁRIOS DA UEMS, 2018)
This paper examines expressions of male heterosexual identity present in Michel Laub’s O diário da queda and Luiz Ruffato’s Inferno Provisório. Heterosexual masculinity is nearly always oriented towards the past (unlike feminism, which is nearly always oriented towards the future), and Michel Laub and Luiz Ruffato both reveal a keen sensitivity to masculinity’s backward-looking orientation by exploring contemporary masculinity’s toxic manifestations: male violence and aggression, male fears of feeling or expressing emotion, male fears of emasculation, male detachments from committed relationships, etc. In so doing, these authors challenge typical narratives of masculinity that idealize the past. Instead, these authors present past-oriented narratives that are essentially anti-nostalgic. In doing so, both Laub and Ruffato adopt the strategies of feminism in working to turn masculinity’s orientation towards the future.